Age-dependent cardioprotective action of meldonium on heart remodeling under the experimental hypoosmolar hyperhydration (Bangladesh Journal of Medical Science, 2019)
Background: Chronic water overload leads to a remodeling of the internal organs, in particular the heart. The reaction of the organism to the influence of the damaging factors varies depending on age. Therefore, the complex treatment of diseases, which results in a positive water balance, requires the prescription of cardioprotectors.The aim of our study was the determination of morphological changes of the heart of rats of different age under the influence of hypoosomolar hyperhydration and an attempt to correct the detected changes by means of meldonium.Material and Method:The experiment was conducted on 36 laboratory male rats of two age groups: young (3 months old), and old (22 months old).Modeling of severe degree ofhypoosmolarhyperhydration was by the introduction of 10 ml distilled water three times a day and synthetic analogue of antidiuretic hormone «Minirin» (Ferring) 2 times a day at a dose of 0.01 mg without meldonium (first experimental series) and with the parallel introduction of meldonium (second experimental series). We analyzed organometric and histomorphometric data to study the features ofthe heart remodeling.Results: The organometric study indicated a uniform increase in the weight of the ventricles and a significant dilatation of the right ventricular cavity in young ratsof the first experimental series, and there was a predominant increase in the weight of the right ventricle and uniform dilatation of the cavities of both ventricles in old animals of the same series. The histomorphometric study has determined increasing in the diameter of cardiomyocytes and their nuclei in both age groups. We observed increasing in the relative amount of cardiomyocytes and vessels, and decreasing in relative amount of connective tissue in young rats. In contrast, there was decreasing in relative amount of cardiomyocytes and vessels, and increasing in the relative amount of connective tissue in old animals. The meldonium administration positively acts on the right ventricle, slowing its dilatation in young rats of the second experimental series and its hypertrophy in old rats. Moreover, the diameter of cardiomyocytes in both age groups is significantly increased, but meldonium stabilizes the diameter of the nuclei of cardiomyocytes. Also meldonium increases in the relative amount of vessels in 3-month age rats.Conclusions: The use of meldonium to correct the morphofunctional state of myocardium in rats under the influence of severe degree of Hypoosmolar hyperhydration significantly reduces the damaging effect of water overload on the myocardium of young animals, and to a lesser extent, on the myocardium of animals of old age. The positive effect of meldonium on the heart of experimental rats is to enhance myocardial vascularization, slowing the growth of the weight of the chambers of the heart, and slowing the dilation of ventricular cavities.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.395-401